Publishing romance fiction in the Philippines - McAlister, Jodi; Parnell, Claire; Trinidad, Andrea Anne (Cambridge elements. Elements in publishing and book culture, 2023)
The romance publishing landscape in the Philippines is vast and complex, characterised by entangled industrial players, diverse kinds of texts, and siloed audiences. This text maps the large, multilayered, and highly productive sector of the Filipino publishing industry.